Poverty And Gini Ratio On Human Development Index In West Sumatera - Hidayat, Rahmat; Silvia, Engla Desnim; Ariani, Fatma (GOVERNORS, 2025)
This study aims to test and prove the effect of poverty and the Gini ratio on the human development index in the Regency/City of West Sumatra, the population in this study is the Central Statistics Agency (BPS) of West Sumatra Province from 2016 to 2020, while the sample in this study was 95 samples of the human development index, poverty and the Gini ratio in West Sumatra. The type of data used is panel data. Data was obtained from the official website of the Central Statistics Agency of West Sumatra Province (BPS) Data was processed using SPSS 22. The results show that the Gini ratio has a positive and significant influence on the Human Development Index in West Sumatra, suggesting that income distribution dynamics play an important role in shaping human development outcomes. In contrast, poverty was found to have no statistically significant effect on HDI, indicating that other factors may moderate or buffer the impact of poverty at the regional level. The novelty of this research lies in its specific regional focus on West Sumatra and its use of panel data across multiple years and districts to uncover nuanced relationships that may not be visible in broader national-level analyses. Additionally, by comparing poverty and income inequality side by side, this study offers a fresh perspective on which socio-economic indicators most strongly influence human development in decentralized governance settings like Indonesia.